ROLE OF INTUITING TYPE EDUCATORS IN INDONESIAN MI / SD LEARNING - Sumaryanti, Lilis (Jurnal Bahasa Lingua Scientia, 2018)
A teacher must be creative in sorting and selecting and can develop standards in shaping the competence of learners. While the competencies that must be possessed by educators include pedagogic, professional, social and personality. These four competencies are very important in supporting the learning process because they are interrelated with each other. This is a separate obstacle for educators / homeroom teachers when teaching Indonesian language subjects at the MI / SD level which are still monotonous in the learning process. Teachers who have creative, professional, and fun nature are students’ expectations and these three traits are usually owned by intuiting type educators. The intuitive type is a personality dominated by the right brain. Usually these types of people have advantages, which are creative and like improvising. The development of creative thinking skills and improvisation in concepts as well as the use of appropriate methods, strategies and media can be used as a foundation for MI / SD Indonesian teachers in creating conducive learning according to learning objectives.